2004
DOI: 10.1093/pcp/pch014
|View full text |Cite
|
Sign up to set email alerts
|

Function, Intracellular Localization and the Importance in Salt Tolerance of a Vacuolar Na+/H+ Antiporter from Rice

Abstract: We examined the function and intracellular localization of the product of the Na(+)/H(+) antiporter gene (OsNHX1) cloned from rice (Oryza sativa). OsNHX1 has the ability to suppress Na(+), Li(+) and hygromycin sensitivity of yeast nhx1 mutants and sensitivity to a high K(+) concentration, a novel phenotype of the nhx1 mutants. Analysis using rice cells expressing a fusion protein of OsNHX1 and green fluorescent protein and Western blot analysis using antibodies specific for OsNHX1 confirmed the localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
233
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(252 citation statements)
references
References 42 publications
16
233
1
2
Order By: Relevance
“…In plants, the significant contribution of the NHX1 homologue to salt tolerance is well documented (59,60). Interestingly, blocking a related kinase, Ca 2ϩ -dependent protein kinase, results in increases in [Na ϩ ] cyt in rice cells due to the lack of activation of a likely vacuolar Na ϩ /H ϩ antiporter (3).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the significant contribution of the NHX1 homologue to salt tolerance is well documented (59,60). Interestingly, blocking a related kinase, Ca 2ϩ -dependent protein kinase, results in increases in [Na ϩ ] cyt in rice cells due to the lack of activation of a likely vacuolar Na ϩ /H ϩ antiporter (3).…”
Section: Discussionmentioning
confidence: 99%
“…77 The overexpression of the Na + /H + antiporter gene clone from OsNHX1, improved the salt tolerance of transgenic rice cells and plants. 73 The role of tonoplast Na + /H + antiporter in plant salt tolerance has been reinforced by several evidences showing that exposure to salt promotes the increase of Na + /H + antiport activity 35,42,46,51,53,97,98 (Fig. 3).…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 96%
“…3). Some reports show upregulation of NHX genes, 22,56,[72][73][74][75][76][77]79,80,99 increased protein abundance 56,[74][75][76] or regulation at protein activity level. 46,100 Garbarino and co-workers 97,100 have shown that the inducible Na + /H + antiporter activity observed in tonoplast from barley roots grown in the presence of NaCl was due to activation of an existing protein rather than to de novo protein synthesis, since the rapid induction was observed in the presence of inhibitors of protein synthesis.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis (Arabidopsis thaliana), the plasma membrane Na 1 /H 1 antiporter SOS1 catalyzes Na 1 extrusion from cells (Shi et al, 2003). Vacuolar sequestration of Na 1 is also effective at lowering Na 1 concentration in the cytoplasm and is mediated by the NHX family of vacuolar Na 1 /H 1 antiporters, such as AtNHX1 in Arabidopsis (Apse et al, 1999) and OsNHX1 in rice (Fukuda et al, 2004). HKT-type transporters are involved in regulating cation homeostasis under salt stress in Arabidopsis (Sunarpi et al, 2005) and rice (Ren et al, 2005).…”
mentioning
confidence: 99%